2017
DOI: 10.1111/1748-5967.12233
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temporal data aggregation on the perceived structure of a quantitative plant–floral visitor network

Abstract: Seasonal turnover in plant and floral visitor communities changes the structure of the network of interactions they are involved in. Despite the dynamic nature of plant–visitor networks, a usual procedure is to pool year‐round interaction data into a single network which may result in a biased depiction of the real structure of the interaction network. The annual temporal dynamics and the effect of merging monthly data have previously been described for qualitative data (i.e. describing the occurrence of inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 36 publications
(62 reference statements)
3
11
0
1
Order By: Relevance
“…Meanwhile, the winter season had two additional distinct features: specialized visitor groups (Lepidoptera) were more species-rich, and more specialized plants were blooming during this period. In this study, all network qualitative properties showed significant seasonal variations of a single network through its annual cycle which were consistent with previous studies [42,49,50]. The seasonal changes in nestedness, network-level specialization and modularity suggest that species exhibited more specialized interactions during the season when the number of species and interactions were at a minimum.…”
Section: Network Structure and Seasonalitysupporting
confidence: 91%
See 2 more Smart Citations
“…Meanwhile, the winter season had two additional distinct features: specialized visitor groups (Lepidoptera) were more species-rich, and more specialized plants were blooming during this period. In this study, all network qualitative properties showed significant seasonal variations of a single network through its annual cycle which were consistent with previous studies [42,49,50]. The seasonal changes in nestedness, network-level specialization and modularity suggest that species exhibited more specialized interactions during the season when the number of species and interactions were at a minimum.…”
Section: Network Structure and Seasonalitysupporting
confidence: 91%
“…The seasonal changes in nestedness, network-level specialization and modularity suggest that species exhibited more specialized interactions during the season when the number of species and interactions were at a minimum. The similar results were also found in subtropical climate areas [50]. Since specialization is not affected by system size and sampling intensity [32]; our findings regarding seasonal variations in specialization seem robust.…”
Section: Network Structure and Seasonalitysupporting
confidence: 87%
See 1 more Smart Citation
“…Network mesoscale structures derive from node degree distributions, which in mutualistic networks are highly skewed, with few highly generalized species and a long tail of specialists Jonhson et al, 2013;Sajjad et al, 2017). Numerous studies suggest that observed degree distributions result from neutral processes, such as highly skewed abundances or sampling-related issues, which ultimately result in large differences in species' detection probabilities (Ollerton et al, 2003;Vázquez & Aizen, 2004;Vázquez et al, 2005Vázquez et al, , 2009Kallimanis et al, 2009;Araujo et al, 2010).…”
Section: Why a Core-periphery Structure?mentioning
confidence: 99%
“…For instance, current practices involve the quantification of network properties on data that is aggregated temporally, disregarding temporal dynamics despite these communities show high turnovers of species and interactions, with a highly skewed distribution of species' phenophases, and a network structure that evolves seasonally (Ollerton et al, 2003;Vázquez et al, 2005Vázquez et al, , 2009Olesen et al, 2008;Petanidou et al, 2008;Kallimanis et al, 2009;Araujo et al, 2010;Zhang et al, 2011;Falcão et al, 2016;Sajjad et al, 2017;Kantsa et al, 2018). In addition to skewed degree distributions, mutualistic networks tend to have a high degree of disassortativity, that is, specialist species tend to interact with generalists (Vázquez & Aizen, 2004;Jonhson et al, 2013).…”
Section: Why a Core-periphery Structure?mentioning
confidence: 99%